Trilling as a sociolinguistic variable: Ethnicity and variation in the Hebrew dorsal fricatives - Gafter, Roey J. (Sociolinguistic Studies, 2021)
In the speech of many Hebrew speakers, the distinction between the voiceless pharyngeal fricative /?/ and its non-pharyngeal counterpart is neutralized, with the non-pharyngeal production becoming increasingly common. Although this is a well-studied phenomenon, little attention has been given so far to the possibility of meaningful variation in the non-pharyngeal forms. In this paper I demonstrate that the non-pharyngeal dorsal variant is not always a fricative, but rather, is often realized as a trill. Using data from sociolinguistic interviews conducted in two field sites in Israel, I show that the rate of trilling varies among speakers, and is sensitive to both social and linguistic factors. A key finding is that speakers who do not produce pharyngeals are more likely to produce the trill variant, but only in one of the two communities studied, in which the loss of the pharyngeals is considerably more advanced. While retention of the pharyngeals is strongly associated with Mizrahi (Middle Eastern and North African) descent, variation in trill rates interacts with ethnicity in complex ways, which shed light on the social and linguistic dynamics underlying the spread of the non-pharyngeal forms.